2023
DOI: 10.1021/acsomega.3c01441
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Metabolomics and Network Pharmacology to Explore the Mechanism of Tongmai Yangxin Pills in Ameliorating Doxorubicin-Induced Cardiotoxicity

Abstract: Doxorubicin (DOX) is a broad-spectrum chemotherapeutic drug used in clinical treatment of malignant tumors. It has a high anticancer activity but also high cardiotoxicity. The aim of this study was to explore the mechanism of Tongmai Yangxin pills (TMYXPs) in ameliorating DOX-induced cardiotoxicity through integrated metabolomics and network pharmacology. In this study, first, an ultrahigh-performance liquid chromatography−quadrupole-time-of-flight/mass spectrometry (UPLC−Q-TOF/MS) metabonomics strategy was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was found that TMYXP could enhance anti-OS ability and reduce apoptosis by regulating signaling pathways such as Nrf2/HO-1 and p38-MAPK( Cui et al, 2018 ). Network pharmacology and metabolomics studies suggest that TMYXP can attenuate Dox-induced myocardial injury by regulating the upstream protein signaling pathway of insulin, MAPK, p53, and other signaling pathways, as well as regulating energy metabolism ( Shu et al, 2023 ).…”
Section: Effects Of Chinese Herbal Medicine and Its Constituent Compo...mentioning
confidence: 99%
“…It was found that TMYXP could enhance anti-OS ability and reduce apoptosis by regulating signaling pathways such as Nrf2/HO-1 and p38-MAPK( Cui et al, 2018 ). Network pharmacology and metabolomics studies suggest that TMYXP can attenuate Dox-induced myocardial injury by regulating the upstream protein signaling pathway of insulin, MAPK, p53, and other signaling pathways, as well as regulating energy metabolism ( Shu et al, 2023 ).…”
Section: Effects Of Chinese Herbal Medicine and Its Constituent Compo...mentioning
confidence: 99%